(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract - Over the last decade, Automatic Speech Recognition (ASR)—have advanced substantially. The field has undergone a fundamental transformation with the introduction of end-to-end models, and its development has been further accelerated by recent developments in attention-based techniques and transfer learning on large- This paper compares state-of-the-art techniques in detail and provides a thorough review of research done in Hindi ASR since 2010. It examines modern methods for both monolingual and multilingual systems with an emphasis on deep learning models. This study examines multiple models on publicly available speech datasets to evaluate their performance for practical implementation. It also discusses open-source ASR research findings, challenges, and future directions, especially in mitigating data dependency, improving generalizability across low-resource languages, handling speaker variability, and operating in noisy conditions.